2015
DOI: 10.1182/asheducation-2015.1.400
|View full text |Cite
|
Sign up to set email alerts
|

The use of novel monoclonal antibodies in the treatment of acute lymphoblastic leukemia

Abstract: Regardless of age, patients with relapsed or refractory acute lymphoblastic leukemia (ALL) have extremely poor outcomes. The success of reinduction chemotherapy remains dismal, because complete remission rates are low and seldom durable. Clearly, new and novel strategies are needed to improve the outcome of patients with relapsed or refractory ALL. Patients with early relapse, especially those still receiving chemotherapy, tend to have a much poorer outcome and are often chemotherapy resistant. Although high-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
0
10
0
3
Order By: Relevance
“…The rationale for the use of monoclonal antibodies is that lymphoblasts express various cell-surface antigens that may be favourable targets for this therapy. For instance, over 95% of B-cell ALL and more than 90% of lymphoblasts express CD19 and CD22, respectively (32). Monoclonal antibody therapy has been recently used in clinical trials to treat children and adults with relapsed or refractory ALL.…”
Section: Adolescent and Young Adult Acute Lymphoblastic Leukaemiamentioning
confidence: 99%
“…The rationale for the use of monoclonal antibodies is that lymphoblasts express various cell-surface antigens that may be favourable targets for this therapy. For instance, over 95% of B-cell ALL and more than 90% of lymphoblasts express CD19 and CD22, respectively (32). Monoclonal antibody therapy has been recently used in clinical trials to treat children and adults with relapsed or refractory ALL.…”
Section: Adolescent and Young Adult Acute Lymphoblastic Leukaemiamentioning
confidence: 99%
“…Apart from this standard approach, novel treatment methods have been also proposed in the recent decade, including monoclonal antibodies [42], immuno-chemotherapy [43], interferon-α-maintenance therapy [44], radio-immunotherapy [45], and stem cell transplantation [46]. Despite promising results, most of these methods are in preclinical or clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The follow up phase III, randomized control trial comparing INO with standard of care treatment in adult patients with ALL, Study NCT01564784 (INO-VATE Trial), revealed the superiority of INO [82,83]. Two hundred and eighteen adults were randomized to receive either weekly doses of INO (0.8 mg/m 2 on day 1 followed by 0.5 mg/m 2 on days 8 and 15) or standard of care, intensive chemotherapy.…”
Section: Immunotherapymentioning
confidence: 99%